Transforming tuberculosis (TB) service delivery model in China: issues and challenges for health workforce - Ziyue Wang; Weixi Jiang; Yuhong Liu; Lijie Zhang; Anna Zhu; Shenglan Tang; Xiaoyun Liu (BMC, 2019)
Abstract Background China's TB control system has been transforming its service delivery model from CDC (Centers for Disease Control and Prevention)-led model to the designated hospital-led model to combat the high disease burden of TB. The implications of the new service model on TB health workforce development remained unclear. This study aims to identify implications of the new service model on TB health workforce development and to analyze whether the new service model has been well equipped with appropriate health workforce. Methods The study applied mixed methods in Zhejiang, Jilin, and Ningxia provinces of China. Institutional survey on designated hospitals and CDC was conducted to measure the number of TB health workers. Individual questionnaire survey was conducted to measure the composition, income, and knowledge of health workers. Key informant interviews and focus group discussions were organized to explore policies in terms of recruitment, training, and motivation. Results Zhejiang, Jilin, and Ningxia provinces had 0.33, 0.95, and 0.47 TB health professionals per 10 000 population respectively. They met the national staffing standard at the provincial level but with great variety at the county level. County-designated hospitals recruited TB health professionals from other departments of the same hospital, existing TB health professionals who used to work in CDC, and from township health centers. County-designated hospitals recruited new TB health professionals from three different sources: other departments of the same hospital, CDC, and township health centers. Most newly recruited professionals had limited competence and put on fixed posts to only provide outpatient services. TB doctors got 67/100 scores from a TB knowledge test, while public health doctors got 77/100. TB professionals had an average monthly income of 4587 RMB (667 USD). Although the designated hospital had special financial incentives to support, they still had lower income than other health professionals due to their limited capacity to generate revenue through service provision. Conclusions The financing mechanism in designated hospitals and the job design need to be improved to provide sufficient incentive to attract qualified health professionals and motivate them to provide high-quality TB services.